The Good Farmer: Morality, Expertise, and Articulations of Whiteness in Zimbabwe. Issue 1 (2nd January 2018) - Suzuki, Yuka
ABSTRACT: In Zimbabwe, land has always been a visible index of racial domination and oppression. Following independence in 1980, the redistribution of white property to black farmers emerged as one of the most contentious battlegrounds for refiguring citizenship and nationhood. This article explores how white farmers in a small community in western Zimbabwe fought to establish claims to belonging as they faced the threat of imminent land reform at the turn of the millennium. Drawing upon Tania Li's concept of articulation [2000. "Articulating Indigenous Identity in Indonesia: Resource Politics and the Tribal Slot." Comparative Studies in Society and History 42 (1): 149–179], I suggest that farmers constructed themselves both as moral subjects who cared for the environment, and skilled subjects with the technical know-how to safeguard and maximise the country's resources. In the absence of claims to indigeneity, farmers attempted to offset their own compromised morality by invoking the language of expertise. By examining this intersection between morality and expertise, I argue that white farmers in Zimbabwe brought together logics typically imagined to be distinct as a strategy to claim moral belonging while obscuring the historical and political factors that threatened to void those same claims.